The Performance Improvement of the Low-Cost Ultrasonic Range Finder (HC-SR04) Using Newton's Polynomial Interpolation Algorithm - Gutama Indra Gandha; Dedi Nurcipto (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2019)
The ultrasonic range finder sensors are widely used sensor in many applications such as computer applications, general purpose applications, medical applications, automotive applications and industrial grade applications. The ultrasonic range finder sensor has many advantages. The advantages are easy to use, fast in measuring process, non-contact measurement and suitable for air and underwater environment. However, the ultrasonic range finder has deviation especially for low-cost sensor. It affects the accuracy level of the measurement result that performed by its sensor directly. The HC-SR04 categorized as a low-cost ultrasonic range finder sensor. This sensor has significant error level. The improvement of the accuracy level of this low-cost ultrasonic sensor is expected to this research. The Newton's polynomial interpolation algorithm has been used in this research to reduce the error during the measurement process. The implementation of Newton's polynomial interpolation has succeeded to improve the sensor accuracy. The MSE level of 29,96 is obtained without the Newton's Polynomial Interpolation implementation. The implementation of the Newton's Polynomial Interpolation algorithm has succeeded to increase the accuracy level of the sensor by 55,54%. It has been proofed by the decrease of MSE level by 13,32.